Zoonotic pathogens in wild Asian primates: a systematic review highlighting research gaps - Patouillat, Laurie; Hambuckers, Alain; Adi Subrata, Sena; Garigliany, Mutien; Brotcorne, Fany (Frontiers in Veterinary Science, 2024)
Ongoing global changes, including natural land conversion for agriculture and urbanization, modify the dynamics of human-primate contacts, resulting in increased zoonotic risks. Although Asia shelters high primate diversity and experiences rapid expansion of human-primate contact zones, there remains little documentation regarding zoonotic surveillance in the primates of this region. Using the PRISMA guidelines, we conducted a systematic review to compile an inventory of zoonotic pathogens detected in wild Asian primates, while highlighting the coverage of primate species, countries, and pathogen groups surveyed, as well as the diagnostic methods used across the studies. Moreover, we compared the species richness of pathogens harbored by primates across diverse types of habitats classified according to their degree of anthropization (i.e., urban vs. rural vs. forest habitats). Searches of Scopus, PubMed, and the Global Mammal Parasite Database yielded 152 articles on 39 primate species. We inventoried 183 pathogens, including 63 helminthic gastrointestinal parasites, 2 blood-borne parasites, 42 protozoa, 45 viruses, 30 bacteria, and 1 fungus. Considering each study as a sample, species accumulation curves revealed no significant differences in specific richness between habitat types for any of the pathogen groups analyzed. This is likely due to the insufficient sampling effort (i.e., a limited number of studies) which prevents drawing conclusive findings. This systematic review identified several publication biases, particularly the uneven representation of host species and pathogen groups studied, as well as a lack of use of generic diagnostic methods. Addressing these gaps necessitates a multidisciplinary strategy framed in a One Health approach which may facilitate a broader inventory of pathogens and ultimately limit the risk of cross-species transmission at the human-primate interface. Strengthening the zoonotic surveillance in primates of this region could be realized notably through the application of more comprehensive diagnostic techniques such as broad-spectrum analyses without a priori selection.